Marketing Optimization: Purchase Data-Based Customer Segmentation Decision Support System - Wong, Vinncent Alexander; Fadhiilah, Muhammad Althaaf; Santoso, Dzikry Aji; Setyorini, Luthfia Rahmi; Amrani, Andi Ahyar Almuhajir; Mursityo, Yusi Tyroni (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2025)
Abstract—In the era of technological development and changes in shopping culture, e-commerce is increasingly dominating the market, and customer purchase data is becoming a valuable source of information for companies. To address the challenges of inappropriate targeting, customer retention, customer satisfaction, and measuring the effectiveness of marketing campaigns, this research aims to design a decision support system for customer segmentation based on purchase data, identify the optimal parameters of clustering algorithms, and develop appropriate marketing strategies for each group of customers generated from clustering. By using tools such as Matplotlib, Numpy, and Pandas, this research is expected to provide valuable guidance for companies in optimizing their marketing strategies in the competitive e-commerce market.